EFFECT OF BALANCED NUTRITION ON YIELD AND NUTRIENT UPTAKE OF PEA (PISUM STIVUM L.) UNDER INDO-GANGETIC PLAINS OF INDIA - D. K. SINGH, A. K. SINGH SANJAY KUMAR SINGH MANDHATA SINGH O. P. SRIVASTAVA (The Bioscan, 2015)
A field experiment was conducted for two consecutive years (2006-07 and 2007-08) during rabi season to study the effect of balanced nutrition on growth, nodulation, yield, physiological and agronomic efficiencies of pea (Pisum stivum L.). Results showed that the higher fertility level (60-40-5, P2O5-S-Zn Kg/ha) was found most effective in enhancing the plant height, dry matter accumulation, nodulation, yield attributes and finally led to 0.29 t/ha (3.25 t/ha) higher seed yield over lowest fertility levels (30-20-2.5, P2O5-S-Zn Kg/ha). Fertility level F2 registered higher nutrient uptake by seed (103.6, 14.7 and 12.5 kg/ha N, P and S, respectively) and Stover (73.4, 10.3 and 12.19 kg/ha N, P and S, respectively) of pea. However, agronomic efficiency of P, S and Zn and physiological efficiency of N, P and S were highest with F1 treatment over F2. Among the micronutrients application, integrated use of Mo, Co and B produced taller plant (115.78cm.), more dry matter (accumulation/plant (8.79g), maximum nodule number (44.50) and weight (36.95 mg) over control and alone application of micronutrients. Seed yield and nutrient uptake by seed and stover were also found higher with combined use of micronutrients.